2018
DOI: 10.22598/mt/2018.30.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Can New Product Selling and Innovation in Sales Be Improved by Using Internal Marketing and Empowerment?

Abstract: Purpose-The purpose of this paper is to investigate the impact of internal marketing and empowerment on new product selling and sales innovativeness. The link between sales innovativeness and new product selling was examined as well. Design/Methodology/Approach-Data was collected through a questionnaire aimed at sales professionals. PLS structural equation modeling was applied to analyze the data. Findings and implications-The results show that internal marketing (IM) and empowerment positively aff ect new pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Psychological empowerment is an intrinsic task motivation reflecting a sense of self-control and active involvement in work roles (Seibert et al, 2011). Numerous studies have revealed that empowered employees display greater work enthusiasm and job performance (Ružić & Benazić, 2018;Shruti et al, 2016). According to the self-determination theory (Ryan & Deci, 2000), this study suggests that a sense of empowerment perceived by salespeople can boost positive work ability, including adaptive selling.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Psychological empowerment is an intrinsic task motivation reflecting a sense of self-control and active involvement in work roles (Seibert et al, 2011). Numerous studies have revealed that empowered employees display greater work enthusiasm and job performance (Ružić & Benazić, 2018;Shruti et al, 2016). According to the self-determination theory (Ryan & Deci, 2000), this study suggests that a sense of empowerment perceived by salespeople can boost positive work ability, including adaptive selling.…”
Section: Introductionmentioning
confidence: 85%
“…Psychological empowerment manifested into four cognitions: meaning, competence, self-determination, and impact (Thomas & Velthouse, 1990). Existing literature on personal selling has emphasized that a salesperson who feels empowered relates to an increase in new product selling, sales innovativeness (Ružić & Benazić, 2018), and job performance (Simintiras et al, 2013). Recent studies revealed that adaptive selling is significantly affected by how salespeople perceive their work (Rigolizzo et al, 2022).…”
Section: Psychological Empowerment and Adaptive Selling Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on salesperson empowerment and innovative selling are increasing (Ružić & Benazić, 2018;Grass, Backmann, & Hoegl, 2020;Asgari & Nikokar, 2016), which indicates that empowerment has a critical role in innovation success. However, in the context of small businesses, Kmieciak et al (2012) still found inconclusive research findings.…”
Section: Introductionmentioning
confidence: 99%